Reconstructing Islamic Boarding School Education in the Digital Era: Integrating Spiritual Pedagogy and Neuroscience-Based Learning - Nashrul Mu'minin; Nuraini Rahmawati; Faysa Alya Ma'arif (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study examines the reconstruction of Islamic boarding school education in contemporary technological society by critically combining moral-religious instruction, digital adaptation, and neuroscience-based learning. Rapid developments in technology have reshaped educational practices, generating both opportunities and challenges for Islamic residential schooling systems, particularly in preserving students’ spiritual identity while supporting cognitive growth. This research aims to explore how neuroscience-informed learning strategies can enhance the effectiveness of moral and religious instruction within technology-supported learning environments. The study employs a qualitative approach with a critical-analytical design. Data were collected through literature review, document analysis, and in-depth interviews with educators in Islamic boarding schools. The findings indicate that the application of neuroscience principles in Islamic education improves student engagement, emotional regulation, and internalization of moral values. In addition, the use of digital tools, when aligned with value-based instruction, contributes to a more holistic and meaningful learning experience. The study emphasizes that reforming Islamic boarding education requires a balanced synergy between tradition and innovation. In conclusion, neuroscience-informed and technology-responsive approaches can significantly support the development of a more adaptive, relevant, and transformative Islamic education system.